Is socially responsible investing (SRI) in stocks a competitive capital investment? A comparative analysis based on the performance of sustainable stocks - Ann-Kathrin Blankenberg; Jonas F. A. Gottschalk (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
In the last few decades, socially responsible investments (SRI) have growingly become a relevant issue. The market size in the United States grew from less than a trillion US Dollars to 8.72 trillion US Dollars in 2016, in the past 20 years (US SIF 2016). Approximately 11 trillion Euro was invested in sustainable investments in Europe (EuroSIF 2016). Previous research focused on SRI mutual funds but rarely on green stocks for different reasons. Investing directly in stocks can have different advantages than investment in mutual funds. This article focus on the risk-adjusted competitiveness of a sustainable portfolio based on stocks. We show that a sustainable portfolio does not perform significantly different than a conventional one. The consideration of sustainable criteria does not influence the investment result negatively and could be applied by investors without the need to sacrifice returns.
Keywords: 330; Socially Responsible Investing; Sharpe Ratio; sustainable portfolios; ethical investing